Species of Fusarium on Pinus radiata in New Zealand - Dick, M.A.; Dobbie, K. (New Zealand Plant Protection, 2002)
The common diseases of pines caused by Fusarium species in New Zealand are dampingoff and root rot disorders of seedlings in forest nurseries The emergence of pine pitch canker disease caused by Fusarium subglutinans f sp pini as a serious threat to Pinus radiata plantations has increased the need for an awareness of the species associated with pines in New Zealand Standard morphological procedures were used to identify Fusarium cultures isolated from diseased pines and from soil in forest nurseries Fusarium oxysporum and F solani were the most commonly found species in bareroot P radiata nurseries and were obtained from both seedlings and from soil The species most frequently obtained from branches and needles of older trees in plantations were F avenaceum and F sambucinum but these were not associated with serious disease